Bibliographic reviews in Cuban medical journals. - Lucitere Rodríguez González (Medisur)
Background: Bibliographic reviews acquire great importance in the specific context of medical publications; however, some editorial facts can affect their scientific value. Objective: To characterize the bibliographic reviews published by some Cuban medical journals. Methods: The most recent reviews (10) were analyzed by means of an exploratory, retrospective and descriptive study. Selected from 5 electronic medical journals, summing up 50 articles. The following variables were studied: article's length, statement of objective and characteristics of bibliographic references. Results: In 20 reviews the objective was not stated, only in 23 (46%) the objective was correctly declared. More than 50% of the article had between 4 and 9 screens; 16 structural variables were found with a predominance of blocks and block plus discussion. Only 20 (40%) gathered between 25 and 50 references and 24 had more than 50% of their references not updated. Conclusion: There is a misapprehension regarding the review article among Cuban medical journals, which could somehow affect its pertinence and scientific rigor to the eyes of the international scientific community.